Efektifitas Penggunaan Media Pembelajaran 3D Hologram dalam Meningkatkan Hasil Belajar Peserta Didik Di SMA Negeri 2 Majene - Ridsa, Ardiansyah; Sideng, Uca; Suprapta, Suprapta (LaGeografia, 2020)
The research is aimed to know : How is the effectiveness of the use of media learning 3D Hologram in improving outcomes study participant students in SMA Negeri 2 Majene . The method of research is using research experiments with design research nonrandomized control group pretest-posttest design . The subjects in this study were students of class XII IPS in SMA Negeri 2 Majene . Technique Â  analysis of the data in the study using the help of SPSS 24 for windows. To test the hypothesis used -t test ( independent samples t test ). The results of the study end showed that H 0 : Î¼ 1 = Î¼ 2 rejected and H A : Î¼ 1 > Î¼ 2 is received , so it can be concluded that the scores of students who use the medium of 3D hologram is higher than the students who get teaching is conventional . Advice for teachers who want to use the medium of learning 3D hologram of this can be done as an alternative to increasing the power attractiveness of participant learners against the material of learning . Suggested also conducted research over further to : a) examine the effectiveness of the use of 3D hologram media in mataeri, variables, as well as different locations, b) developing a 3D hologram presentation models, not only in form but in the form of video applications.